The given function is
f(x) = x^3 - 1
We want to find the inverse of the function, f^-1(x). The first step is th replace f(x) with y. It becomes
y = x^3 - 1
The next step is to interchange x and y and solve for y. We have
x = y^3 - 1
Adding 1 to both sides of the equation, we have
x + 1 = y^3 - 1 + 1
y^3 = x + 1
Taking the cube root of both sides of the equation, we have
To plot the graph of the the inverse of the function, we would substitute values of x into the function and find corresponding values of y. These x and y values would be plotted on the graph. We have
The graph is shown below